Review essay: The young Hayek - Ivo Maes (National Bank of Belgium, 2023)
Friedrich Hayek has been one of the dominating intellectual figures of the 20th century. Hayek, together with Gunnar Myrdal, received the 1974 Nobel Memorial Prize in economics, for "their pioneering work in the theory of money and economic fluctuations and for their penetrating analysis of the interdependence of economic, social and institutional phenomena". Bruce Caldwell (Duke University) and Hansjoerg Klausinger (WU Vienna University of Economics and Business), two distinguished historians of economic thought, have produced a massive (840 pages) work, covering the first five decades of Hayek's existence. Hayek: A Life, 1899-1950 is a monumental and sympathetic biography. The book is based on painstaking archival research and shows great scholarship. The novelty is very much in bringing the person of Hayek to life, with its strengths and weaknesses.
Keywords: B20; B31; B53; E14; G28; N10; P00; 330; Friedrich Hayek; Austrian school; biography; business cycle theory